Residual Kidney Function Decline and Mortality in Incident Hemodialysis Patients - Obi, Yoshitsugu; Rhee, Connie M.; Mathew, Anna T.; Shah, Gaurang; Streja, Elani; Brunelli, Steven M.; Kovesdy, Csaba P.; Mehrotra, Rajnish; Kalantar-Zadeh, Kamyar (Journal of the American Society of Nephrology, 2016)
In patients with ESRD, residual kidney function (RKF) contributes to achievement of adequate solute clearance. However, few studies have examined RKF in patients on hemodialysis. In a longitudinal cohort of 6538 patients who started maintenance hemodialysis over a 4-year period (January 2007 through December 2010) and had available renal urea clearance (CL urea ) data at baseline and 1 year after hemodialysis initiation, we examined the association of annual change in renal CL urea rate with subsequent survival. The median (interquartile range) baseline value and mean±SD annual change of CL urea were 3.3 (1.9–5.0) and −1.1±2.8 ml/min per 1.73 m 2 , respectively. Greater CL urea rate 1 year after hemodialysis initiation associated with better survival. Furthermore, we found a gradient association between loss of RKF and all-cause mortality: changes in CL urea rate of −6.0 and +3.0 ml/min per 1.73 m 2 per year associated with case mix–adjusted hazard ratios (95% confidence intervals) of 2.00 (1.55 to 2.59) and 0. 61 (0.50 to 0.74), respectively (reference: −1.5 ml/min per 1.73 m 2 per year). These associations remained robust against adjustment for laboratory variables and ultrafiltration rate and were consistent across strata of baseline CL urea , age, sex, race, diabetes status, presence of congestive heart failure, and hemoglobin, serum albumin, and serum phosphorus levels. Sensitivity analyses using urine volume as another index of RKF yielded consistent associations. In conclusion, RKF decline during the first year of dialysis has a graded association with all-cause mortality among incident hemodialysis patients. The clinical benefits of RKF preservation strategies on mortality should be determined.